Exploring the perceived impact of cultural differences on ethical behavior of expatriate managers and their Czech team members - Grishaeva, Elina; Procházka, David Anthony; Vrbová, Lucie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The diploma thesis focused on individual experiences of expatriate Russian managers and their Czech subordinates with regards to their perception of ethical and unethical behavior and the influence of the cultures on the perception. In order to fulfill the goal of the research, the qualitative research methodology was selected to discover what is perceived effect of cultural differences between Russian managers and Czech subordinates with regards to ethical behavior and obtain in-depth understanding on the topic. It was revealed that national culture is perceived as auxiliary factor influencing behavior in the context of work as well as perception of ethics. Nevertheless, as the main factor highlighted by the participants of the research – personality – is highly interconnected with the background, which is contingent upon national culture, it shall remain as focus area for the consequent researches. In addition to that, it was found out that perception and judgement of ethical component of behavior is highly contingent upon perspective and attitude towards consequences, and the parties affected by the consequences.
Vedoucí práce: David Anthony Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses